2019
DOI: 10.1002/cncr.32064
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and young adult cancer survivorship: The new frontier for investigation

Abstract: Adolescent and young adult cancer survivors are at long‐term risk of early mortality. More research is needed to understand these risks and to develop effective interventions with the expectation that this group may be unique compared with other age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Participants were randomly assigned to either the exercise intervention group or control group following baseline assessment. Participants were stratified according to gender and treatment intensity (high vs moderate; adapted from the Intensity of Treatment Rating Scale 3,48 (Supporting Information Table S2) and randomized by block randomization with a 1:1 allocation using mixed block sizes of 2 and 4. Allocation was concealed by opaque envelopes at the coordinating site.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were randomly assigned to either the exercise intervention group or control group following baseline assessment. Participants were stratified according to gender and treatment intensity (high vs moderate; adapted from the Intensity of Treatment Rating Scale 3,48 (Supporting Information Table S2) and randomized by block randomization with a 1:1 allocation using mixed block sizes of 2 and 4. Allocation was concealed by opaque envelopes at the coordinating site.…”
Section: Methodsmentioning
confidence: 99%
“…With five-year survival for adolescents and young adults (AYA) with cancer now exceeding 80%, 1,2 a growing number of survivors are at risk of the physical and psychosocial complications of cancer and its treatment. 3,4 In particular, cardiorespiratory fitness is reduced in cancer survivors across the age spectrum. This often persists into longterm survivorship, and is associated with increased cardiovascular disease risk and late mortality.…”
Section: Introductionmentioning
confidence: 99%
“…AYA trial enrollment disparities on both pediatric and adult clinical trials have been noted in prior studies, which translates to fewer AYAs having access to innovative therapies and challenges in evaluating potential differences in therapy toxicities. 10,15,[23][24][25][26][27][28][29][30][31] Even among AYAs that do enroll on trials and have more structured follow-up guidelines, our study found that they have significantly higher loss to follow-up rates compared to their younger counterparts. The results of these analyses among clinical trial participants shed light on inequities in long-term follow-up and suggest that the loss to follow-up rate may be even higher in AYAs not enrolled on trials.…”
Section: Discussionmentioning
confidence: 51%
“…AYA trial enrollment disparities on both pediatric and adult clinical trials have been noted in prior studies, which translates to fewer AYAs having access to innovative therapies and challenges in evaluating potential differences in therapy toxicities 10,15,23–31 . Even among AYAs that do enroll on trials and have more structured follow‐up guidelines, our study found that they have significantly higher loss to follow‐up rates compared to their younger counterparts.…”
Section: Discussionmentioning
confidence: 54%
“…Advances in cancer treatment have led to increased survival rates, however, even if patients survive and are cured, they are still at risk of the development of long-term medical (e.g., cardiovascular disease or second malignancies) or psychosocial (e.g., high distress levels [ 17 ], financial toxicity due to unemployment without a prior career job) long-term and late effects of cancer and its treatment, that may also increase the risk of late mortality [ 18 , 19 , 20 , 21 , 22 ]. The impact and consequences cancer has on AYA, including the gap in survival outcomes, differs from other age groups for several reasons [ 23 ]: Insufficient awareness of cancer risk and symptoms among AYA and healthcare professionals resulting in prolonged diagnostic trajectories [ 24 , 25 ]; Unique and incompletely understood tumor biology—cancers that are histologically indistinguishable across the age spectrum may be characterized by particular biological features in the AYA population [ 9 , 26 , 27 ]; Distinct age-related physiology, pharmacology, and genomic properties with respect to cancer susceptibility and treatment [ 9 ]; Unequal access to and low participation rates in clinical trials [ 1 ]; Lack of age-adjusted treatments [ 28 ] and age-specific psychosocial care—”I am treated like my 74-year-old grandma” [ 29 , 30 ]; Adolescence and emerging and young adulthood are complex phases of life due to the many physical, emotional, cognitive, and social transitions [ 31 ].…”
Section: Introductionmentioning
confidence: 99%